Well-Being of Lesbian, Gay, Bisexual Youth: The Influence of Rural and Urban Contexts on the Process of Building Identity and Disclosure - Agueli, Barbara; Celardo, Giovanna; Esposito, Ciro; Arcidiacono, Caterina; Procentese, Fortuna; Carbone, Agostino; Di Napoli, Immacolata (Frontiers in Psychology, 2022)
The study investigates how the territorial community can influence individual and social well-being of LGB youth and especially the recognition of their feelings and the construction of their own identity as well as their needs to be socially recognized. This research focuses on the experiences of 30 LGB individuals (23 males and 7 females), with a mean age of 25.07 years (SD = 4,578), living in urban and rural areas of Southern Italy. Focalized open interviews were conducted, and Grounded Theory Methodology, supported by the Atlas.ti 8.0 software, was used for data analysis. The textual material was first coded, and then codes were grouped into five macro-categories: Freedom of identity expression in urban and rural context, Identity construction and acceptance process, Need of aggregation and identification with the LGB community, Role of the interpersonal relationship in the process of identity acceptance, Socio-cultural context and LGB psychological well-being. The results showed a condition common to the two contexts that we can define as 'ghettoization'. Young LGB is alone in the rural area due to a lack of places and people to identify with and greater social isolation. On the contrary, although there are more opportunities in the urban area, young people feel stigmatized and ghettoized because "their places" are frequented exclusively by the LGBTQ community. The work will extensively discuss the limitations of the research, future proposals, and the practical implications of the results.